2022
DOI: 10.1039/d1ta07613b
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional metal–organic framework Mo3(C2O)12 as a promising single-atom catalyst for selective nitrogen-to-ammonia conversion

Abstract: The development of single-atom catalysts (SACs) for electrocatalytic nitrogen reduction reaction (NRR) remains a great challenge. Using density functional theory calculations, we design a new family of two-dimensional metal-organic frameworks...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
5
13
0
Order By: Relevance
“…These results revealed that these three Fe-MOF monolayers could maintain their original atomic structures at a high temperature of 500 K, implying their exceptional thermal stability. The high stability may result from the large π-bonds of high-symmetric sp 2 -C atoms in graphene nanosheets, which agrees with previous work [ 22 , 27 ]. Notable are the slight up and down changes in the plane.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results revealed that these three Fe-MOF monolayers could maintain their original atomic structures at a high temperature of 500 K, implying their exceptional thermal stability. The high stability may result from the large π-bonds of high-symmetric sp 2 -C atoms in graphene nanosheets, which agrees with previous work [ 22 , 27 ]. Notable are the slight up and down changes in the plane.…”
Section: Resultssupporting
confidence: 92%
“…To optimize the atomic structures of these three Fe-MOFs, the variations of energies vs. the lattice constants are also shown in Figure 1 , their lattice constants are optimized to be 12.61 Å for Fe-NH MOF, 12.31 Å for Fe-O MOF, and 13.65 Å for Fe-S MOF, respectively ( Table 1 and Table S1 ). These optimized lattice constants agree with previous investigations [ 22 , 26 , 27 ]. The bond lengths of Fe-N, Fe-O, and Fe-S are 1.85 Å, 1.83 Å, and 2.15 Å, respectively, and the bond lengths of C-N, C-O, and C-S are 1.35 Å, 1.30 Å, and 1.74 Å, respectively, due to differences in the atomic radius of N (r = 70 pm), O (r = 66 pm), and S (r = 104 pm).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations